FORMULASI SEDIAAN TETES MATA DENGAN ZAT AKTIF KOMBINASI KLORAMFENIKOL DAN ZINK SULFAT - Abidin, Zainal (Jurnal Ilmiah As-Syifaa, 2011)
A research has been done to formulate eye drop with chloramphenicol and zinc sulfat as active ingredient. The planned formulation contain chloramphenilcol 0,25%, zink sulfat 0,25%, boric acid 1,9%, methylparaben 0,1%, and water steril until 100 %. To still keep stability of eye drop so added additional ingredient such as Boric acid as buffer, methylparaben as preservative, and water steril as carrier. Result of the research that purity concentration of chloramphenicol in eye drop is 98,62% and zink sulfat is 108,2% as active ingredient approriate with standart of indonesia,s Pharmacope fourth edition. Sterility test shown that eye drop chloramphenicol and zink sulfat there is not found microbe or free from microbe aerob, anaerob, and mold.Key words             : eye drop, chloramphenicol, Zink sulfat